Ordered mesoporous TiC–C composites as cathode materials for Li–O2 batteries. Issue 13 (12th January 2016) - Qiu, Feilong; He, Ping; Jiang, Jie; Zhang, Xueping; Tong, Shengfu; Zhou, Haoshen
Abstract : Ordered mesoporous TiC–C (OMTC) composites were prepared and served as catalysts for nonaqueous Li–O2 batteries. The OMTC cathodes showed high specific capacity, low overpotential and good cyclability. Furthermore, the discharge and charge processes were investigated extensively by XRD, XPS and in situ GC-MS methods. Abstract : Ordered mesoporous TiC–C (OMTC) composites were prepared and served as catalysts for nonaqueous Li–O2 batteries. The OMTC cathodes showed high specific capacity, low overpotential and good cyclability. Furthermore, the reaction mechanism of Li–O2 batteries during charge and discharge processes was investigated extensively by XRD, XPS and in situ GC-MS methods.